A systematic review protocol examining the effect of environmental cardiovascular and antidiabetic agents on aquatic organisms and humans - Nanda Gamad; Shobhit Bhansali; Samir Malhotra (International Journal of Noncommunicable Diseases, 2021)
Context: Pharmaceuticals are released into the environment through human and industrial waste and waste due to handling. They significantly contaminate aquatic systems and through food chain, enter the body of human beings. The development of new techniques such as liquid chromatography and mass spectrometry has helped to detect and measure even the trace amounts of pharmaceutical compounds in the environment. At present, cardiovascular and antidiabetic agents are one of the most commonly prescribed drugs worldwide owing to chronicity of the diseases. However, there is a lack of knowledge regarding their effects on aquatic organisms and human beings once they are released into the environment. Aim: The aim of the study is to identify the extent and characteristics of the toxicity caused by environmental cardiovascular and antidiabetic agents on aquatic organisms and humans. Settings and Design: It will be systematic review of all original research articles which assess the environmental toxicity of one or more cardiovascular and antidiabetic drugs. Methodology: This systematic review will be conducted in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data regarding acute and chronic toxicities caused by cardiovascular and antidiabetic drugs to fish, daphnia, algae, and humans will be collected. In addition, we will report sampling strategies and methodologies adopted to quantify drugs from the samples.